2018
DOI: 10.1021/acsomega.8b00080
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of Fluorescent Sensors with Mixed Aromatic Bicyclic Fused Rings and Pyridyl Groups: Solid Mediated Selective Detection of 2,4,6-Trinitrophenol in Water

Abstract: For a strategic incorporation of both π-electron-rich moieties and Lewis basic moieties acting as hydrogen bonding recognition sites in the same molecule, two new fluorescent sensors, N , N ′-bis(anthracen-9-ylmethyl)- N , N ′-bis(pyridin-2-ylmethyl)butane-1,4-diamine ( banthbpbn , 1 ) and N , N ′-bis(naphthalen-1-ylmethyl)- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…Also, the detection of NAs has gained considerable attention because of their toxicity and high solubility in water . These chemicals are found to be core components of various industrial explosives and environmentally deleterious substances; therefore, effective detection of NAs is crucial for security and environmental concerns. …”
Section: Introductionmentioning
confidence: 99%
“…Also, the detection of NAs has gained considerable attention because of their toxicity and high solubility in water . These chemicals are found to be core components of various industrial explosives and environmentally deleterious substances; therefore, effective detection of NAs is crucial for security and environmental concerns. …”
Section: Introductionmentioning
confidence: 99%
“…70b Also, the detection limit of 2 is higher and comparable with other probes performed in water such as organic probes: H 2 ATAIA (120 ppb), 32 [45][46][47][48][49] The K SV values of 1 and 2 are higher than other reported organic probes such as probes tagged with naphthalene (3.43 Â 10 3 M À1 and 2.69 Â 10 4 M À1 ), 24,25 benzimidazole (1.58 Â 10 4 M À1 ), 27 anthracene (1.77 Â 10 4 M À1 ) 16 and fluorescein (2.10 Â 10 4 M À1 ) 31 and comparable with that of other anthracene (8.08 Â 10 4 M À1 and 7 Â 10 4 M À1 ), 25,32 fluorene (3.90 Â 10 4 M À1 ) 16 and MOF probes such as [Tb(BTC)] n (3.9 Â 10 4 M À1 ), 49c {Zr 6 O 4 (OH) 4 (L) 6 } n (2.9 Â 10 4 M À1 ), 45 [Cd(NDC) 0.5 (PCA)] n (3.9 Â 10 4 M À1 ) 40 and TB-Zn-CP (4.37 Â 10 4 M À1 ) 49d based sensors (Table S4, ESI †). On comparing the detection limits with the two sensors recently reported by our group, 62 it was observed that the sensing ability is improved by the variation of the spacer and increasing Lewis basic nitrogen sites. In addition, the K SV value of 1 is higher than its naphthalene analogue (3.26 Â 10 4 M À1 ).…”
Section: Mechanism Of Action For Tnp Detectionmentioning
confidence: 84%
“…This non-linearity can be allocated to self-absorption or an energy transfer process between the sensor and analyte. 1,32,62 In comparison, the SV plots for other analytes are almost a linear curve, thereby suggesting that either static or dynamic quenching is involved. 72 For TNP, the K SV values were found to be (3.55 AE 0.09) Â 10 4 and (4.97 AE 0.08) Â 10 4 M À1 , respectively in 1 and 2 (Fig.…”
Section: Mechanism Of Action For Tnp Detectionmentioning
confidence: 98%
See 2 more Smart Citations